Searching the Academy (Soushuyuan搜書院): A Chinese Opera as Rule of Law and Legal Narrative - Elaine Y.L. Ho; Johannes M.M. Chan (Law Text Culture, 2014)
In earlier scholarship on traditional societies that became colonised, relations between imported legal systems and indigenous customs that had long operated with quasi-legal effect are often studied in terms of conflict and opposition, to show how western or European institutions progressively displaced what existed before their arrival. In her more recent studies of legal pluralism, however, Lauren Benton argues persuasively from many historical examples and cases that indigenous culture and contingent historical situations are major forces that mediate legal development and change. Though acknowledging her debt to Homi Bhabha’s theorising of hybridised subjects and their disruptions of asymmetrical colonial relations, Benton nonetheless critiques Bhabha’s assumption of ‘a preexisting and relatively constant cultural divide’ (Benton and Muth 2000).